India’s balancing act in the Indo-Pacific : multi-alignment and tilt to the U.S. - Karuturi, Ramyashri Rao (Nanyang Technological University, 2020)
This dissertation aims to examine the nature of India’s strategic partnerships against the backdrop of the Indo-Pacific and addresses the question of how it is balancing these relationships. The main argument put forth is that India is balancing two approaches with respect to its Indo-Pacific strategy. The first is the broader multi-alignment framework in which it is consolidating its maritime cooperation through a range of strategic partnerships. The second, which is interlinked with the first approach, involves strengthening India-U.S. ties in this sphere given the increasingly aligned interests between the two powers. This paper will explore the multi-alignment framework through the lens of the expanding India-U.S. relationship. This is studied using cases of India’s strategic partnerships with Japan, Australia, France, China, Russia, Iran, Indonesia, Vietnam, and Singapore. This dissertation concludes that while key partnerships have been augmented by India’s tilt to the U.S., in large part due to the nature of the defence relations between them and common vision for the region, there have been significant constraints to India’s other partnerships. However, New Delhi’s commitment towards strategic autonomy has allowed these constraints to be limited in nature, further justifying the importance of an alignment with the U.S. rather than an alliance. Moving forward, in order to secure and develop these ties without the label of a being a ‘reluctant’, ‘uncertain’, or an ‘evasive’ partner, India would likely benefit from advancing the multilateral initiatives it partakes in by focusing on other avenues.